Penerapan Internet of Things Pada Kandang Jangkrik Berbasis Arduino Uno R3 - Santoso, Lilik Hari; Ramadhan, Sachrur; Anwar, Nizirwan; Setiawan, Iwan; Santosa, Nugroho Budhi (Fakultas Teknik Universitas Persada Indonesia YAI, 2024)
The development and advancement of technology today are becoming increasingly complex,with one of the significant advancements being the Internet of Things (IoT) technology. IoT hasbeen implemented in various sectors, particularly in the livestock sector. However, there are stillissues where cricket farmers continue to use conventional methods in the breeding process,resulting in suboptimal processes and leading to the death of their livestock. The aim of thisresearch is to develop a system that applies IoT technology to assist cricket farmers in managingthe breeding process within cricket enclosures. These farmers face challenges in feeding theircrickets and controlling the temperature and humidity within the enclosures.The research methodis carried out by collecting needs, designing a system in the form of a system design, andimplementing the system. The system uses Arduino uno R3 as a control center, RTC DS3231 as atimer for feed using a servo motor, DHT11 to detect temperature and humidity in the cage whichwill activate the fan and heating lamp as a solution. The system uses the NodeMCU ESP8266 wifimodule which is connected to the Blynk application to monitor temperature and humidity in thecage. With this system, it helps make it easier for cricket farmers in the cultivation process.